2020
DOI: 10.1002/ajmg.a.61559
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, molecular, and pathological findings in a Neu–Laxova syndrome stillborn: A Brazilian case report

Abstract: Neu-Laxova syndrome (NLS) is a lethal genetic multiple congenital anomaly syndrome of unknown prevalence representing the severe spectrum of serine biosynthesis defects associated with PHGDH, PSAT1, or PSP gene mutations. The purpose of this study was to describe clinical/molecular and pathologic features of a NLS case caused by novel heterozygous missense variant in PHGDH gene identified in his consanguineous parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…13 Following these recent discoveries, some cases have already been described with the genetic study and the identification of the mutation involved. 10,16 Regarding genetic diagnosis, the initial chromosomal evaluation should be followed by the whole exome sequencing analysis, as verified in the case presented.…”
Section: Discussionmentioning
confidence: 82%
“…13 Following these recent discoveries, some cases have already been described with the genetic study and the identification of the mutation involved. 10,16 Regarding genetic diagnosis, the initial chromosomal evaluation should be followed by the whole exome sequencing analysis, as verified in the case presented.…”
Section: Discussionmentioning
confidence: 82%
“…The phenotype ranges from nonspecific developmental delay (Tabatabaie et al, 2011) to the severe lethal disease known as Neu–Laxova syndrome (NLS; MIM# 256520). Following the first descriptions by Neu and Laxova in 1971 and 1972, respectively (Laxova, Ohara, & Timothy, 1972; Neu, Kajii, Gardner, & Nagyfy, 1971), fewer than 100 cases of NLS have been reported to date (Acuna‐Hidalgo et al, 2014; Bourque et al, 2019; Cavole et al, 2020; Coto‐Puckett et al, 2010; El‐Hattab et al, 2016; Manning, Cunniff, Colby, El‐Sayed, & Hoyme, 2004; Mattos et al, 2015; Ni et al, 2019; Shaheen et al, 2014). The clinical hallmarks of this disorder are severe intrauterine growth restriction (IUGR), microcephaly, cutaneous abnormalities, and distinctive craniofacial features including sloping forehead, ocular hypertelorism, prominent eyes, ectropion, flat nose, round gaping mouth, micrognathia, short neck, and low‐set malformed ears.…”
Section: Introductionmentioning
confidence: 98%
“…PHGDH gene mutations are associated with two kinds of disease phenotypes: classical PHGDH deficiency (OMIM: 601815) and Neu–Laxova syndrome (NLS, OMIM: 256520). Since first reported by Jaeken et al (1996), a total of 43 patients with the PHGDH gene variants were identified in 23 articles (Abdelfattah et al, 2020; Acuna‐Hidalgo et al, 2014; Benke et al, 2017; Brassier et al, 2016; Cavole et al, 2020; de Koning et al, 1998; el‐Hattab et al, 2016; Glinton et al, 2018; Häusler et al, 2001; Jaeken et al, 1996; Klomp et al, 2000; Kraoua et al, 2013; Mattos et al, 2015; Méneret et al, 2012; Ni et al, 2019; Pind et al, 2002; Pineda et al, 2000; Poli et al, 2017; Shaheen et al, 2014; Tabatabaie et al, 2009, 2011; Takeichi et al, 2018; Tao & Lu, 2021). An overview of clinical characteristics in patients who were reported with clear genetic etiology of PHGDH gene mutations is summarized in Data S1.…”
Section: Introductionmentioning
confidence: 99%